2006
DOI: 10.1021/bi052349a
|View full text |Cite
|
Sign up to set email alerts
|

Folding Kinetics of the S100A11 Protein Dimer Studied by Time-Resolved Electrospray Mass Spectrometry and Pulsed Hydrogen−Deuterium Exchange

Abstract: This study reports the application of electrospray ionization (ESI) mass spectrometry (MS) with on-line rapid mixing for millisecond time-resolved studies of the refolding and assembly of a dimeric protein complex. Acid denaturation of S100A11 disrupts the native homodimeric protein structure. Circular dichroism and HSQC nuclear magnetic resonance measurements reveal that the monomeric subunits unfold to a moderate degree but retain a significant helicity and some tertiary structural elements. Following a rapi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
68
0

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 51 publications
(68 citation statements)
references
References 72 publications
0
68
0
Order By: Relevance
“…HX-MS has been widely used in solution phase for analysis of protein conformation and dynamics (23)(24)(25), as well as structural changes upon a variety of state transitions, such as folding/unfolding (26), ligand binding (27), and self-association (28,29). Further, Li et al carried out hydrogen/deuterium exchange in protein powders to measure the effects of lyophilization and excipients on protein structure (30).…”
Section: Introductionmentioning
confidence: 99%
“…HX-MS has been widely used in solution phase for analysis of protein conformation and dynamics (23)(24)(25), as well as structural changes upon a variety of state transitions, such as folding/unfolding (26), ligand binding (27), and self-association (28,29). Further, Li et al carried out hydrogen/deuterium exchange in protein powders to measure the effects of lyophilization and excipients on protein structure (30).…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of different ion charge state distribution (CSD) envelopes derived from different protein conformations is one of the methods for monitoring protein structural transition by ESI-MS (Chowdhury et al 1990;Loo et al 1991). ESI-MS has proven particularly useful for detection and characterization of folding/unfolding intermediates (Grandori 2002;Haq et al 2005;Wintrode et al 2005) and for kinetic studies of protein structural transitions (Konermann 2004;Furdui et al 2006;Pan et al 2006). It has been well documented that an unfolded protein molecule can accommodate more protons upon desolvation than can a compact native protein molecule because of the increased solvent-exposed surface area (Mohimen et al 2003).…”
mentioning
confidence: 99%
“…45 The acid-denatured state of S100A11 has been characterized by electrospray ionization (ESI) MS, CD, and NMR spectroscopy. 46 These techniques revealed that acid exposure induces complete dimer dissociation. The free subunits exhibit a greatly diminished NMR chemical shift dispersion at pH 2, indicating major perturbations in tertiary structure.…”
Section: Introductionmentioning
confidence: 99%
“…Time-resolved ESI-MS has previously been used to examine the mechanism of this process at the intact protein level. 46 It was found that the reaction proceeds through a burst-phase monomeric intermediate. Pulsed HDX suggested the formation of additional transient species, although the isotope exchange data were convoluted and did not provide clear insights into the reaction mechanism.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation